Lithuanianization of Catholic Services in the Parish of Vandžiogala in 1918–1940 - Mačiulis, Dangiras (Acta humanitarica academiae Saulensis, 2025)
In the Republic of Lithuania in 1918–1940 the Lithuanian political elite sought the dominance of the Lithuanian language in all areas of public life, including churches. There were also conflicts over the use of language in Catholic churches during services – in ethnically mixed parishes, disputes arose over which language should dominate during services. In Catholic parishes, there was a dispute over the use of Lithuanian and Polish languages in church services. The article examines the conflict regarding the use of Polish and Lithuanian languages during services in St. Trinity Church of Vandžiogala Catholic parish in 1918–1940, the congregation of which was absolutely dominated by Polish-speaking believers. It is said that the effort to Lithuanianize the service in Vandžiogala parish, where most of the parishioners spoke Polish, was the initiative of the ethnically Lithuanian local elite that formed in the local town. Acting from nationalistic motives and ignoring the ethnic composition of the parishioners, they sought to exclude the Polish language from services in the parish church and ensure the dominance of the Lithuanian language. This became the reason for the conflict in the parish between the Polish and Lithuanian believers. The political regime did not directly intervene in the resolution of the conflict, but indirectly supported Lithuanianization. The church and the clergy basically supported the aspiration to Lithuanianize the service in the parish church. All proponents of the Lithuanianization course were united by their attitude towards the Polish-speaking inhabitants of the parish – the latter were considered not Poles, but Polish-speaking Lithuanians whose ancestors were Polonized, so the real ethnic composition of the parish inhabitants was ignored and the effort to Lithuanianize them was justified.
Keywords: nationalism; Lithuanian language; Republic of Lithuania 1918-1940; Catholic Church; Vandžiogala